Bacterial vaginosis and the risk of early miscarriage in women undergoing intracytoplasmic sperm injection cycles: a prospective cohort study. (2nd October 2018) - Moini, Ashraf; Mohammadi Yeganeh, Ladan; Shiva, Marzieh; Ahmadieh, Malihe; Salman Yazdi, Reza; Hasani, Fatemeh; Bagheri Lankarani, Narges; Sanati, Azam
Abstract: This study aimed to assess the possible association of bacterial vaginosis (BV) and early miscarriage in 408 women undergoing intracytoplasmic sperm injection (ICSI) for reasons of male infertility. A vaginal sample was obtained before oocyte retrieval and evaluated for BV-associated bacteria using the Nugent scoring system. The primary outcome was early miscarriage and the secondary outcomes included implantation, pregnancy, late miscarriage, preterm delivery and live birth rates. Chi-square, ANOVA, relative risk and odds ratio were used for data analysis where appropriate. The prevalence of BV was estimated as 7.3%. From 336 patients who had embryo transfer, 138 patients (41.1%) conceived. A total of 17% ( n = 23) of pregnant women miscarried during the first trimester: 15 patients (15%) were normal, 4 (17.4%) were intermediate and 4 (26.7%) patients had BV ( p = 0.52). The relative risk of early miscarriage in BV patients compared to the non-BV and intermediate group was 1.77 (0.68–4.64, 95% CI). Implantation, pregnancy, preterm delivery and live birth rates were comparable between groups. We conclude that BV does not appear to have an adverse impact on outcomes in women being treated with ICSI for male factor infertility and is not associated with miscarriage and preterm birth.